Formation of human Capital in the informal and its interaction in the Congolese economy. - Kagni, Vintor (Advances in Social Sciences Research Journal, 2018)
This reseach aims to highlight the formation of human capital in the informal sector as well as its collective and individual valorization in Congolese economic. The socio-economic reproduction of formal education in the informal sector, with 70.1% of activities and 75% of jobs in the Congo, makes it possible to overcome market and state failures. The formation of human capital in informality passes through channels linked to social, physical and natural capital through inter- and extra-referential interaction, which contribute to the integration of populations, to the development of their capabilities and to the Consolidation of human capital in the determination of endogenous growth. The modeling of informal and formal interaction shows that the expected utility of the informal with an intensity of 72 seems more important than that of the formal one evaluated at 59. The two sectors are complementary and allow the populations to improve their property Be in one as in the other according to the capacities of each and the economic opportunities with a view to ensuring social stability and security.